Primary percutaneous coronary intervention for acute ST-segment elevation myocardial infarction: changing patterns of vascular access, radial versus femoral artery. Issue 19 (12th July 2009) - Hetherington, S L; Adam, Z; Morley, R; de Belder, M A; Hall, J A; Muir, D F; Sutton, A G C; Swanson, N; Wright, R A
Abstract : Objective: To examine the safety and efficacy of emergency transradial primary percutaneous coronary intervention for ST-elevation myocardial infarction. Design: Single-centre observational study with prospective data collection. Setting: A regional cardiac centre, United Kingdom. Patients: 1051 consecutive patients admitted with ST-elevation myocardial infarction, without cardiogenic shock, between November 2004 and October 2008. Interventions: Percutaneous coronary interventions by radial and femoral access Main outcome measures: The primary outcome measures were procedural success, major vascular complication and failed initial access strategy. Secondary outcomes were in-hospital mortality and major adverse cardiac and cerebrovascular events, needle-to-balloon times, contrast volume used, radiation dose absorbed and time to discharge. Multiple regression analysis was used to adjust for potential differences between the groups. Results: 571 patients underwent radial access and 480 femoral. A variable preference for radial access was observed among the lead operators (between 21% and 90%). Procedural success was similar between the radial and femoral groups, but major vascular complications were more frequent at the site of femoral access (0% radial versus 1.9% femoral, p = 0.001). Failure of the initial access strategy was more frequent in the radial group (7.7% versus 0.6%, p<0.001). Adjustment for other procedural and clinical predictors did not alter these findings. Needle-to-balloon time, as a measure of procedural efficiency, was equal for radial and femoral groups. Conclusions: In the setting of acute ST-elevation myocardial infarction without cardiogenic shock, transradial primary angioplasty is safe, with comparable outcomes to a femoral approach and a lower risk of vascular complications.